CONCEPTION OF BILINGUAL INTERCULTURAL EDUCATION IN INDIGENOUS PEOPLES OF THE GUIANA REGION - Álvarez, Carla Zulimar Pérez; Barreto, Gilberto Enrique Resplandor (Seven Editora, 2025)
Education is a universal human right to which all people should have access without discrimination of any kind. In Venezuela, the Magna Carta (1999) in Article 102 declares that "it is a human right and a fundamental social duty, it is democratic, free and obligatory. The State will assume it as an undeniable function of maximum interest at all levels and modalities, and as an instrument of scientific, humanistic and technological knowledge at the service of society (...). Similarly, article 121 declares that indigenous peoples have the right to their own education and to an educational regime of an intercultural and bilingual nature, taking into account their socio-cultural particularities, values and traditions, hence bilingual intercultural education is conceived as a modality within the educational system, (...) which is compulsory and inalienable in all schools and educational centers located in regions with indigenous populations.  to the basic education subsystem (Article 27, LOE, 2009). The purpose of this research was to reveal the conception of bilingual intercultural education that the indigenous peoples of the Guayana Region have. The complementarity of the quantitative and qualitative paradigms was used, with the application of a questionnaire and semi-structured interviews with teachers from five schools located in the Gran Sabana. The data were processed by means of content analysis. The most relevant findings show that there is no curriculum of its own in any of the schools, they are governed by the official curriculum and by the school calendar. Teachers are convinced that bilingual intercultural education contributes to the preservation and rescue of their culture and traditions but, in general, ancestral knowledge is not incorporated into the work plans and classes are in Spanish. On the initiative of some teachers, native songs and dances are included at the time of a celebration in the communities. As a consequence, this educational modality is not applied effectively because it does not have pedagogical orientations specific to their ethnic condition, which is why the authorities and teachers demand the creation of a curriculum in accordance with their worldview and traditions that contributes to the revitalization and rescue of their culture.DOI: https://doi.org/10.56238/sevened2025.018-037